The Influence of Adverse Effects on Quality of Life of Survivors of Gynecologic Cancer. Issue 9 (November 2017) - Omichi, Chiaki; Nakamura, Keiichiro; Haraga, Junko; Ida, Naoyuki; Saijo, Masayuki; Nishida, Takeshi; Kusumoto, Tomoyuki; Masuyama, Hisashi
Abstract : Objective: The objective of this observational study was to investigate correlations between adverse effects (lower-extremity lymphedema [LEL], dysuria, and severe gastrointestinal symptoms) and quality of life (QOL) (physical well-being [PWB], social well-being, emotional well-being [EWB], and functional well-being) before treatment, at least 6 weeks after treatment (posttreatment1), and 3 or 6 months after treatment (posttreatment2) of patients with gynecologic cancer (GC). Methods: From August 2012 to October 2016, questionnaire responses and clinical data of 75 patients with GC were collected and assessed by treatment received. The χ 2 test was used to determine the significance of correlations. Results: Participants with LEL had significantly poorer QOL than did those without it in the domains of PWB at posttreatment1 ( P = 0.026) and EWB at posttreatment2 ( P = 0.020). Moreover, patients with 2 adverse effects (LEL plus dysuria or severe gastrointestinal symptoms) had significantly poorer QOL than did those with no or single adverse effect in the domains of PWB at posttreatment1 and posttreatment2 (posttreatment1: P = 0.049, P = 0.001; posttreatment2: P = 0.002, P = 0.028) and poorer QOL compared with those with no adverse effect in the domain of EWB at posttreatment1 ( P = 0.017). Conclusions: Poorer QOL in emotional and physical domains is associated with adverse effects of treatment in patients with GC. It is important to consider the effects of radical therapy not only on survival but also on the QOL of survivors.